A experiência do grupo condutor na implantação do Nasf em Vitória-ES - Calente, Daniele Stange (2017)
This dissertation is interested in narrating a trajectory that follows the work process of the group responsible for implanting the Support Centers for Family Health (NASF) in Vitória - ES. This conducting group was formed of professionals from the central level of the Municipal Health Department (SEMUS) with the purpose of transforming practices of the professionals from the support of the primary health care (psychologists, social workers, speech therapists, professionals of physical education in the health and pharmacists) in NASF teams and they “embraced” that commitment. Considering this transformation as something greater than the accreditation of these professionals to the federal management bodies, the NASF conducting group organized a series of activities and actions in order to support the consolidation of these teams and their practices according to the matrix support logic. It seeks to analyze the issues that this experience produces in the group itself, at the central level of SEMUS, in the primary health care professionals that form the teams and also in the researcher. For this analysis, we used the researcher's field diary and other records such as minutes and memoirs of meetings produced collectively by the conducting group. Taking as a methodological reference the Research-Intervention and the cartographic method, it seeks to develop clues for the problematization of the clinical practices, management and certification in healthcare, enabling the emergence of new practices, that are developed in a collective way and constitute other means of existence.